CDO1 promoter methylation is associated with gene silencing and is a prognostic biomarker for biochemical recurrence-free survival in prostate cancer patients. Issue 12 (1st December 2016) - Meller, Sebastian; Zipfel, Lisa; Gevensleben, Heidrun; Dietrich, Jörn; Ellinger, Jörg; Majores, Michael; Stein, Johannes; Sailer, Verena; Jung, Maria; Kristiansen, Glen; Dietrich, Dimo
ABSTRACT: Molecular biomarkers may facilitate the distinction between aggressive and clinically insignificant prostate cancer (PCa), thereby potentially aiding individualized treatment. We analyzed cysteine dioxygenase 1 (CDO1) promoter methylation and mRNA expression in order to evaluate its potential as prognostic biomarker. CDO1 methylation and mRNA expression were determined in cell lines and formalin-fixed paraffin-embedded prostatectomy specimens from a first cohort of 300 PCa patients using methylation-specific qPCR and qRT-PCR. Univariate and multivariate Cox proportional hazards and Kaplan-Meier analyses were performed to evaluate biochemical recurrence (BCR)-free survival. Results were confirmed in an independent second cohort comprising 498 PCa cases. Methylation and mRNA expression data from the second cohort were generated by The Cancer Genome Atlas (TCGA) Research Network by means of Infinium HumanMethylation450 BeadChip and RNASeq. CDO1 was hypermethylated in PCa compared to normal adjacent tissues and benign prostatic hyperplasia ( P < 0.001) and was associated with reduced gene expression (ρ = −0.91, P = 0.005). Using two different methodologies for methylation quantification, high CDO1 methylation as continuous variable was associated with BCR in univariate analysis (first cohort: HR = 1.02, P = 0.002, 95% CI [1.01–1.03]; second cohort: HR = 1.02, P = 0.032, 95% CI [1.00–1.03]) but failed to reach statistical significance in multivariate analysis. CDO1 promoter methylation is involved in gene regulation and is a potential prognostic biomarker for BCR-free survival in PCa patients following radical prostatectomy. Further studies are needed to validate CDO1 methylation assays and to evaluate the clinical utility of CDO1 methylation for the management of PCa.